Navigating the 'broad freeway': ocean currents and inland isolation drive diversification in the Pandanus tectorius complex (Pandanaceae). (25th December 2016) - Gallaher, Timothy; Callmander, Martin W.; Buerki, Sven; Setsuko, Suzuki; Keeley, Sterling C.
Abstract: Aim: To test for and describe the genetic structure of the Pandanus tectorius complex, a group of closely related ocean‐dispersed plants and members of the Indo‐Pacific coastal strand community. Location: Tropical Indo‐Pacific (coastal East Africa to Polynesia). Methods: We sampled 535 individuals (46 localities) from throughout the range of the complex. Fifteen microsatellite loci were used to detect and characterize population structure and estimate migration rates between island groups and broad regions. Results: Hierarchical population structure was detected. Samples group into an eastern cluster (Hawaii and coastal South‐Central Pacific localities) and a western cluster [Western Pacific (WP) through Indian Ocean]. Within these two clusters, at least six regional subclusters were detected including samples from the Indian Ocean + South China Sea (SCS), Ogasawara Islands, WP, inland South‐Central Pacific, coastal South‐Central Pacific and Hawaii. Migration rates between regions are low leading to isolation and genetic differentiation while within regions, rates are much higher. In most cases, inland populations are genetically differentiated from nearby coastal counterparts. Main conclusions: Substantial population structure occurs across the range of the P. tectorius complex due to dispersal limitation across stretches of open ocean and patterns of ocean currents. Low levels of asymmetric westward migration, consistent with the direction of ocean currents in the Pacific, links Hawaii and the South‐Central Pacific with populations further to the west preventing complete isolation. SCS + Indian Ocean populations are distinct from those in the Pacific due to limited dispersal between these regions. The isolation of inland populations on several islands also contributes to genetic differentiation. While population clusters have a clear geographical basis they are not completely congruent with previously recognized taxa.